Uso de Zeólitas naturais para mitigar a volatilização de amônia na fase inicial da compostagem de dejetos líquidos de suínos - Giacomini, Diego Antonio (2014)
Gaseous losses of nitrogen (N) during composting of pig slurry (PS), mainly due to volatilization of ammonia (NH3), have important environmental and economic implications, requiring technological alternatives for their mitigation. The objective of this study was to evaluate the efficiency of natural zeolites clinoptilolite and stilbite at different doses and in different particle sizes and frequency of addition of clinoptilolite, to mitigate the losses of NH3 in the initial phase of PS composting. For this, experiments were conducted in a pilot scale, lasting between 14 and 17 days, wherein each zeolite was added at increasing doses of 5, 10 and 20% (w / v), the PS formed on a substrate by mixing sawdust (70%) and shavings (30%). In each experiment was performed three to four applications of PS, with or without addition of zeolites, followed by simultaneous plowing, plus three or four additional turnings in the compound. All these experiments were divided in two articles that make up this dissertation. NH3 emissions were reduced with Zeolites when compared to the control treatment only with the application of manure, and the efficiency was directly related to the dose and frequency for both zeolites addition to clinoptilolite. The clinoptilolite was more efficient in reducing ammonia emissions than stilbite and showed no differences between the analyzed particle sizes. The average of all experiments, the reduction in NH3 emissions that clinoptilolite and stilbite provided regarding PS without zeolites was between 24-76% and 8-37%, respectively. These results demonstrate the high potential of natural zeolites, mainly clinoptilolite in mitigating NH3 volatilization during composting of PS.